Mycobacterium fortuitum abdominal wall abscesses following liposuction - Hussam Al Soub; Eman Al-Maslamani; Mona Al-Maslamani (Indian Journal of Plastic Surgery)
we describe here a case of abdominal abscesses due to mycobacterium fortuitum following liposuction. the abscesses developed three months after the procedure and diagnosis was delayed for five months. the clues for diagnosis were persistent pus discharge in spite of broad spectrum antibiotics and failure to grow any organisms on routine culture. this condition has been rarely reported; however, the increasing number of liposuction procedures done and awareness among physicians will probably result in the identification of more cases. combination antibiotic therapy with surgical drainage in more extensive diseases is essential for cure.